Internal iliac artery ligation to combat post partum haemorrhage: an institutional review of case series - Jain, Anushree; Sapkal, Rekha Uttam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Internal iliac artery supplies the pelvic viscera. IIAL is a valuable surgical procedure to control intractable pelvic haemorrhage with the mainstay aim of uterus preservation. There is a reduction of 85% in pulse pressure and 48% in the blood flow in the arteries distal after internal iliac artery ligation. Thus, the expertise to perform IIAL should be present in armamentarium of every obstetrician and gynaecologist. Methods: Retrospective review of 22 cases who have undergone IIAL or Peripartum hysterectomy for management of Post- Partum haemorrhage in the study period of January 2012 till December 2015 in the Department of Obstetrics and Gynaecology of People’s College of Medical Science and Research Centre, Bhopal. Results: Internal iliac artery ligation was performed in 53% out of which 31.8%% was for placenta previa, 4.54% for adherent placenta, 9.1% IIAL for Atonic PPH. Whereas peripartum hysterectomy was performed in 38% cases out of which 13.6% had perforation of uterus. 9% underwent hysterectomy as well as IIAL. Blood loss more than two 2 liters within period of 60-90mins was effectively and dramatically controlled with IIAL. Thus, maternal mortality reduced while preserving fertility. Control of Pelvic hemorrhage was achieved in 100% of cases. Conclusions: Bilateral ligation of the internal iliac arteries is a safe, rapid and very effective method of controlling bleeding from UTERUS and genital tract. It plays a major role in safe guarding the patient from undergoing life threatening consequences due to pelvic haemorrhage.